PERBANDINGAN PRESTASI BELAJAR AKADEMIK ANTARA MAHASISWA BIDIK MISI DAN MAHASISWA NON BIDIK MISI ( STUDI PADA MAHASISWA PRODI S1 PENJASKESREK ANGKATAN 2011 DAN 2012 FIK ) - YUDHA SUCAHYO, ADHI (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Every student in the educational unit are entitled to tuition assistance for those who have good academic potential and not be able to economically and are entitled to scholarships for high achievers. Tuition assistance program bidik misi is dedicated for prospective students who are economically disadvantaged and achievement. Active bidik misi scholarship recipients will strive spirit to finish his studies on time is 4 years. From here student motivation is well formed to complete their S1 study immediately. This study aims to determine whether there are differences between bidik misi students and non-bidik misi in the academic learning achievements for class of 2011 and 2012. This research is non-experimental. Subjects in this study were students prodi S1 penjaskesrek by using a population of 36 bidik misi student and 254 non-bidik misi students.Total of population is 290 students. From the result of statistical calculation can be concluded that there are diffrences in learning outcomes of academic achievement among bidik misi students and non-bidik misi student. Test data showed that the P value (0,000) < value of a (0,05). Because the result median of bidik misi students is 3,34 greater than non-bidik misi students that only 3,15. Keywords: academic learning achievement, bidik misi student, non-bidik misi student.